PEI-PEG-Coated Mesoporous Silica Nanoparticles Enhance the Antitumor Activity of Tanshinone IIA and Serve as a Gene Transfer Vector. (8th November 2021) - Zhu, Yinxing; Yue, Miao; Guo, Ting; Li, Fang; Li, Zhifeng; Yang, Dazhuang; Lin, Mei
Abstract : Tanshinone IIA (TanIIA) and gene therapy both hold promising potentials in hepatocellular carcinoma (HCC) treatment. However, low solubility and poor bioavailability of TanIIA limit its clinical application. Similarly, gene therapy with GPC3-shRNA, a type of short hairpin RNAs (shRNAs) capable of silencing the glypican-3 (GPC3) expression, is seriously limited due to its susceptibility to nuclease degradation and high off-target effects. In the present study, polyethyleneimine (PEI)-polyethylene glycol (PEG)-coated mesoporous silica nanoparticles (MSN-PEG) were used as a drug carrier. By encapsulating TanIIA into MSN-PEG, we synthesized MSN- TanIIA- PEG nanoparticles and observed the involved characteristics. This was followed by exploration of antitumor activity on the HepG2 cell lines in vitro . Meanwhile, in order to construct GPC3-shRNA plasmids, a shRNA sequence targeting GPC3 was synthesized and cloned into the pSLenti-U6 vector. Accordingly, the performance of MSN- PEG as a gene transfer carrier for GPC3-shRNA gene therapy of HCC in vitro was evaluated, including transfection efficiency and DNA binding biological characteristics. The results indicated successful encapsulation of TanIIA in MSN-PEG, which had satisfactory efficacy, favorable dispersity, suitable particle size, and sustained release effect. The in vitro anti-HCC effects of nano-TanIIA were greatly improved, which outperformed free-TanIIA in terms of proliferation and invasion inhibition, as well as apoptosis induction of HCC cells. As expected, MSN-PEG possessed excellent gene delivery capacity with good binding, release, and protection from RNase digestion. Using MSN-PEG as a gene carrier, the plasmids were successfully transfected into HepG2 cells, and both the mRNA and protein expressions of GPC3 were significantly downregulated. It was thus concluded that a sustained release TanIIA delivery system for HCC treatment was synthesized and that MSN-PEG could also serve as a gene transfer carrier for gene therapy. More interestingly, MSN-PEG may be a potential delivery platform that combines TanIIA and GPC3-shRNA together to enhance their synergistic effect.